Gas turbine internal cooling with 180 degree bend channel design - Lim, Zhi Wei (Nanyang Technological University, 2024)
The primary method for maximising the efficiency of aircraft turbine engines is increasing the turbine inlet temperature, thereby prompting the adoption of rib-turbulated cooling techniques to manage the intense thermal loads on the internal walls. Past research into the two-channel turbine blade models had been limited to a symmetric inlet and outlet channel. This resulted in a skewed temperature profile, with the outlet channel experiencing significantly higher temperatures and creep strain. As such, this report explores the possibility of incorporating an asymmetric inlet-outlet channel to have a more balanced distribution of thermal load across both channels to maximise creep and fatigue performance. In addition, the report performs rigorous analysis into the implementation of novel geometries along the 180-degree sharp bend through a truncated comparative analysis, developing modifications to reduce the tip temperature. Computational Fluid Dynamics (CFD) software (ANSYS Fluent) and Finite Element Analysis (FEA) software (ANSYS Mechanical) were integrated to perform a Fluid-Structure Interaction (FSI) analysis under a 3.0% maximum creep strain criterion. This report proposes an asymmetric inlet to outlet width ratio 1.68 in the baseline Straight Rib Model and 1.56 in the V-spline model. Compared with its symmetric counterpart, the baseline model enabled a 16.8% decrease in specific fluid power and 15.2% increase in fatigue performance under the same result criterion. In the case of V-spline, it allowed for a 32°C increase in maximum freestream temperature while using 16.68% less specific fluid power compared to its symmetric counterpart. In the truncated analysis, modifications E-7 (-146.14°C) and D-2 (-114.01°C) were the best in tip temperature reduction. The full FSI analysis was conducted on selected models with turn geometries, with design E-7 bringing about the greatest decrease in tip temperature (197.9°C). The models also had comparable fatigue performance with the unmodified asymmetric V-spline model (-10.50% to +6.29%).